Measuring Consumer Post-Purchase Regret In Skincare Purchases The Impact Of Intellectual Capital On The Soundness Of Islamic Banks In Indonesia (Journal of Business and Management, 2022)
At this time, progress in the world of skincare is growing rapidly. Not only skin care products with non-local brands, local brand skin care products are also starting to develop and can compete with existing local brands. This development is nothing but supported by the progress of the information and communication industry, so that every time a new product or brand appears, it can be marketed properly using all existing marketing strategies. There are so many parties who take advantage of technological advances well, such as creating various kinds of content that can ultimately attract the attention of the market to buy the products they are contesting. However, this indirectly can have a negative impact on consumers. Because, the number of products or brands that appear with all forms of tempting promotions can lead to a bad buying pattern. Activities that can attract the attention of the market can trigger an unexpected buying pattern or also called impulsive buying, besides that a lot of word of mouth that arises from word of mouth can trigger purchases that do not use the process of consideration properly and in the end it can trigger regret. consumers after purchase. This regret will occur and be felt by buyers when the product or brand they get is not appropriate and unable to meet their expectations. In purchasing skin care products, the expectations that consumers have are none other than those that have a positive relationship with the health of their skin. So far, sellers have only focused on how their products can be sold out by consumers and consumers have only focused on the positive impact they will get from the skin care products they will use without thinking about the possibility of getting bad effects from using the product. Then, most of the previous research was discussing marketing strategies and purchase intensity, whereas research related to post-purchase regret is one of the most important things to study. Therefore, this study decided to discuss the causes and effects of post-purchase regret of skin care products. The purpose of this study was to identify and measure the impact of post-purchase regret of skin care products. This research is a qualitative research conducted using grounded research method, namely by interviewing as many as 20 respondents in depth, with criteria who have purchased or used skincare with all their skin types. Ultimately, this study will develop a pre-existing theory related to post-purchase regret. The results of this study are 'Behavioral Consequences' that occur after consumers feel post-purchase regret.Keywords: skincare, impulsive buying, purchase, post-purchase regret, qualitative research,grounded research